2012
DOI: 10.1103/physrevb.86.020408
|View full text |Cite
|
Sign up to set email alerts
|

Shot noise in magnetic tunnel junctions from first principles

Abstract: We compute the shot noise in ballistic and disordered Fe|MgO|Fe tunnel junctions by a wave-function-matching method. For tunnel barriers with 5 atomic layers we find a suppression of the Fano factor as a function of the magnetic configuration. In the antiparallel configuration the shot noise is full up to a threshold bias that indicates the onset of resonant tunneling. We find excellent agreement with recent experiments when interface disorder is taken into account. The statistics of electron transport in meso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In this spirit, we can thus ascribe local transport on the electrical hotspot and background of MgO barriers that are sputter-grown with 0% (10%) oxygen in the argon plasma 27 to M and F/F þ (F/F þ and conduction or VB edges) centres. Electrical noise 26,66 and memristance 32,34 studies across MgO-based MTJs can immediately benefit from the clarified defect-mediated tunnelling potential landscape that we propose here. Research groups that can smoothly vary the MgO barrier thickness across a series of MTJs (for example, ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this spirit, we can thus ascribe local transport on the electrical hotspot and background of MgO barriers that are sputter-grown with 0% (10%) oxygen in the argon plasma 27 to M and F/F þ (F/F þ and conduction or VB edges) centres. Electrical noise 26,66 and memristance 32,34 studies across MgO-based MTJs can immediately benefit from the clarified defect-mediated tunnelling potential landscape that we propose here. Research groups that can smoothly vary the MgO barrier thickness across a series of MTJs (for example, ref.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of intrinsic effects such as magnon and phonon generation on TMR has been documented 18,19 . On the other hand, the impact of structural defects in MgO on tunnelling is only emerging in this otherwise widely studied, canonical spintronic system [20][21][22][23][24][25][26] . Indeed, defects have been qualitatively suspected of accounting for much lower tunnelling barrier heights than expected 12,27 .…”
mentioning
confidence: 99%
“…14,15 It has also been shown experimentally that the Fano factor in a single-barrier magnetic tunnel junction depends on magnetic configuration of the junction, and can be remarkably enhanced for the antiparallel alignment of the electrodes' magnetizations. [16][17][18][19][20] Even more possibilities have been found in double-barrier tunnel junctions with two ferromagnetic electrodes and one ferromagnetic central layer, 21,22 where one can distinguish four magnetic configurations corresponding to different alignments of the magnetic moments of all three magnetic layers. 23 It has also been shown that a simple model based on two well-separated spin channels for electronic transport cannot properly describe the experimental observations without taking into account spin-flip transitions.…”
Section: Introductionmentioning
confidence: 99%
“…As for MTJs with MgO barriers, full SN (F ¼ 1) independent of the magnetic state was observed in epitaxial Fe=MgO=Fe [19]. Then, the noise was examined for ultrathin (less than 1 nm) MgO barriers, where F ' 0:92 was observed in the parallel state [20,21]. Double-barrier magnetic tunnel junctions (DMTJs), with either nanoparticles [22,23] or a continuous magnetic layer as the central electrode [24], have some advantages in comparison with MTJs.…”
mentioning
confidence: 99%